A formação nominal em português: um estudo sintático-semântico de bases enunciativas - Igor Caixeta Trindade Guimaraes (2011)
This research discusses the semantics of nouns, according to the notions of event and encapsulation, pervaded by the instances of memory and present. Proposes the concept of nominal formation as a category of enunciate and also discusses the fundamentals of nominal determination, taking the view that enunciation produce specification demands by withdrawing the nouns of a virtual state of generality. It is reconsidered, in this way, the traditional view according to which the nouns require to complete their sense, being questioned the controversial ideas of deficit and superavit of the grammatical description.More specifically, we discuss the criteria that differentiate nominal complements of adjuncts; the first is defined as the discursive re-encapsulation categories of nouns, while the latter are defined by having an expository function of regulating the reference unit of noun. Finally,designs that determination occurs not only in nominal phrase level, but also at the level of the entire enunciate.